2019
DOI: 10.20517/2394-4722.2018.86
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer metastasis to the stomach

Abstract: Aim: This study focuses on the stomach as an unusual but not rare site of metastasis of breast cancer. Methods: We performed a literature search on gastric metastasis from breast cancer searching for reviews from 2000 to 2018 and case reports from 2013 to 2018. We found 11 reviews and 36 case reports and we compared their findings about important aspects of gastric metastasis, such as disease free survival, overall survival, symptoms, endoscopic findings, therapy, histology, and immunohistochemistry. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
4
1
Order By: Relevance
“…The reported median interval between breast cancer diagnosis and presentation with intestinal metastasis is variable. D'Angelo et al and McLemore et al reported five and seven years, respectively, in different studies [6,7]. Our patient, in contrast, presented two years after diagnosis, although she had a late-stage disease at diagnosis.…”
Section: Discussioncontrasting
confidence: 52%
“…The reported median interval between breast cancer diagnosis and presentation with intestinal metastasis is variable. D'Angelo et al and McLemore et al reported five and seven years, respectively, in different studies [6,7]. Our patient, in contrast, presented two years after diagnosis, although she had a late-stage disease at diagnosis.…”
Section: Discussioncontrasting
confidence: 52%
“…However, even without a family history of gastric cancer, patients with HLBC have a markedly elevated risk of developing occult gastric malignancy 79 . Breast cancer metastasis may need to be excluded in patients with diffuse gastric cancer who also have a history of ILC, as ILC is the most common breast cancer subtype to metastasise to the stomach and morphologically mimics diffuse‐type gastric cancer 80 . Differentiating metastatic breast from primary gastric carcinoma requires a panel of immunohistochemical markers; for example, GATA binding protein 3 (GATA3), oestrogen receptor (ER) and progesterone receptor (PR) positivity supports breast origin, while CK20 and CDX2 positivity is seen in a proportion of gastric carcinomas 81,82 …”
Section: Heritable Breast Cancer Riskmentioning
confidence: 99%
“…Though our patient presented with metastatic ILC to the stomach on first presentation, there have been multiple reports describing metastatic breast cancer to the stomach manifesting years after the initially surgical treatment of breast cancer with disease-free intervals ranging from a few months to up to 30 years [9]. In summary, with its higher propensity for gastrointestinal spread, a high index of suspicion should be present in patients with ILC.…”
Section: Discussionmentioning
confidence: 70%